Stability of the Institutional System in the Light of the Path Dependence Concept – Survey Results - Dawid BORUCINSKI; Slawomir CZETWERTYNSKI; Jakub SUKIENNIK (Communications of International Proceedings, 2021)
Within the concept of path dependence, some processes can be described as subordinate to their history, i.e., their development depends on their historical formation. Thus, a given process develops according to various development paths, which may lead to the achievement of various states of equilibrium. Likewise, institutional transformations are conditioned by past and present events. Events at the beginning of the path may hinder or exclude the possibility of reaching certain states later in the development of the institution. In other words, some development paths may be blocked or difficult to follow. It seems that in the process of forming a stable institutional environment, the so-called equilibrium of the institutional system, which can be understood as a combination of diverse formal institutions, it is vital to consider path dependence. Therefore, the purpose of this article is to describe the phenomenon of path dependence. The article will also describe such elements as the stability level of the Polish institutional system and the assessment of the rule of law of government actions in the era of the COVID-19 pandemic.
Keywords: Institutional Economics; Path Dependence; COVID-19.